Implementation of a Practical Activity-Based Environmental Education Module to Enhance Environmental Awareness of Elementary School Students at Plataran Hayu, Banyuwangi - Magdalena Putri Nugrahani; Rizki Nurfida Pambayun; Iis Ni'matul Jannah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This community service program aims to improve the quality of environmental education services at Plataran Hayu Banyuwangi through the development and implementation of a practical activity-based learning module. Plataran Hayu is a hydroponic farmers’ group that has been actively developing educational services for children since 2023. The program’s implementation methods include socialization, module development, facilitator training, implementation with students, as well as monitoring and evaluation. The results show an increase in students’ understanding of organic farming, hydroponics, and waste management. Facilitators also experienced improved capacity in managing learning activities. The program produced printed and digital modules, teaching aids, tutorial videos, and a competency standards document. The impacts of this program support the implementation of the Merdeka Curriculum and the Pancasila Student Profile Strengthening Project, and contribute to the achievement of the SDGs, IKU, and Asta Cita.